Genome-wide identification and functional analysis of mRNA m6A writers in soybean under abiotic stress - Liu, Peng; Liu, Huijie; Zhao, Jie; Yang, Tengfeng; Guo, Sichao; Chang, Luo; Xiao, Tianyun; Xu, Anjie; Liu, Xiaoye; Zhu, Changhua; Gan, Lijun; Chen, Mingjia (Frontiers in Plant Science, 2024)
N6-methyladenosine (m6A), a well-characterized RNA modification, is involved in regulating multiple biological processes; however, genome-wide identification and functional characterization of the m6A modification in legume plants, including soybean (Glycine max (L.) Merr.), remains lacking. In this study, we utilized bioinformatics tools to perform comprehensive analyses of molecular writer candidates associated with the RNA m6A modification in soybean, characterizing their conserved domains, motifs, gene structures, promoters, and spatial expression patterns. Thirteen m6A writer complex genes in soybean were identified, which were assigned to four families: MT-A70, WTAP, VIR, and HAKAI. It also can be identified that multiple cis elements in the promoters of these genes, which were classified into five distinct groups, including elements responsive to light, phytohormone regulation, environmental stress, development, and others, suggesting that these genes may modulate various cellular and physiological processes in plants. Importantly, the enzymatic activities of two identified m6A writers, GmMTA1 and GmMTA2, were confirmed in vitro. Furthermore, we analyzed the expression patterns of the GmMTAs and GmMTBs under different abiotic stresses, revealing their potential involvement in stress tolerance, especially in the response to alkalinity or darkness. Overexpressing GmMTA2 and GmMTB1 in soybean altered the tolerance of the plants to long-term alkalinity and darkness, further confirming their effect on the stress response. Collectively, our findings identified the RNA m6A writer candidates in leguminous plants and highlighted the potential roles of GmMTAs and GmMTBs in the response to abiotic stress in soybean.